2009 IEEE PES/IAS Conference on Sustainable Alternative Energy (SAE) 2009
DOI: 10.1109/sae.2009.5534861
|View full text |Cite
|
Sign up to set email alerts
|

Impact of optimal charging of electric vehicles on future generation portfolios

Abstract: Some rights reserved. For more information, please see the item record link above. Abstract-Battery electric vehicles are considered by many to be part of a series of measures necessary to reduce global carbon dioxide emissions and dependence on fossil fuel resources. The extent to which this is possible depends on how successfully they can be implemented into the broader system. This paper considers the power systems impact of different vehicle charging regimes. A test system with a high proportion of variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The PHEVs are dispatched according to a preset schedule, and no vehicle-to-grid (V2G) is considered. Article [7] considers the effect of EVs on future generation portfolios and uses a simplified model to dispatch EVs on top of the demand profile. V2G or the use of EVs as reserves was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…The PHEVs are dispatched according to a preset schedule, and no vehicle-to-grid (V2G) is considered. Article [7] considers the effect of EVs on future generation portfolios and uses a simplified model to dispatch EVs on top of the demand profile. V2G or the use of EVs as reserves was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may not be the case when this added demand coincides with existing peaks. This type of analysis is particularly relevant in countries that are planning to produce large amounts of their electrical energy from renewable energy sources [7]. Confining the charging of EVs to off-peak periods could see an increase in the utilisation of existing plant, although the extent to which the charging of EVs is controllable remains uncertain.…”
mentioning
confidence: 99%
“…The time-invariant parameters are to be estimated so that an appropriate probability distribution is fitted to the duration of the trips. The time-invariant parameters are estimated by maximizing the likelihood given in (7). For a given number of driving states, the transition probabilities can be estimated using the approach in [22].…”
Section: Fitting Time-invariant Parametersmentioning
confidence: 99%
“…For this reason, EVs have received increased interest from the scientific community in recent years (detailed literature reviews of the state of the art can be found in [1] and [2]). Special attention has been given to the analysis of the effect of EVs integration on the electricity demand profile [3,4], emissions [5] and social welfare [6,7,8], and to the design of charging schemes that avoid increasing the peak consumption [9,10], help mitigate voltage fluctuations and overload of network components in distribution grids [11], and/or get the maximum economic benefit from the storage capability of EVs within a market environment, either from the perspective of a single vehicle [12,13] or the viewpoint of an aggregator of EVs [14,15]. In all these publications, though, and more generally in the technical literature on the topic, the charging problem of an EV is addressed either by considering deterministic driving patterns, when the focus is placed on the management of a single vehicle, or by aggregating the driving needs of different EV users, when the emphasis is on modeling a whole fleet of EVs.…”
Section: Introductionmentioning
confidence: 99%